Analysis of the Thermo-Mechanical-Chemical Coupled Response of a Lithium-Ion Battery Particle during a Charge-Discharge Cycle. Issue 3 (1st January 2019) - Masmoudi, M.; Moumni, Z.; Bidault, F.
Abstract : This paper documents a coupled mechanical, thermal and chemical model for the electrode particles made of graphite, LMO (Lithium manganese oxide) and NMC (Lithium nickel manganese cobalt oxide) subject to a charge-discharge current. To this end, the set of equation are established using the thermodynamic of irreversible processes theory. The numerical simulation is carried out thanks to COMSOL software. It is shown that the variation of concentration inside the particle induces a heat source different from the dissipation due to Joule effect. Furthermore, the volume change due to lithium intercalation is dominant compared to thermal and elastic strain. For both states of insertion and extraction, the stresses are lower than yield stress and the particles are not likely to crack in their isolated state. A sensitive analysis with respect of diffusion coefficient, particle stiffness, particle radius and current rate is performed. It also found that a moderate external pressure leads to a longer use of the battery.